An Evaluation of the Influence of Environmental, Social and Cultural factors on the Socialization of Traditional Urban Spaces (Case Study: Iranian Markets). (September 2020) - Mahdinezhad, Jamaloddin; Sedghpour, Bahram Saleh; Nabi, Rana Najjari
The 'bazaar', or the marketplace has been one of the most influential bases of the city in terms of social, political and economic development, and is considered as an active public space for initiating fundamental changes in society. Across Islamic cultures and civilizations, as well as their historical precedents, the marketplace has occupied a broad and complex social meaning, especially in Iran. In this research, the marketplace is considered from a socio-commercial point of view. In order to improve the efficiency of public spaces, it is necessary to identify their effective parameters of socialization, and utilize them towards the future design or improvement of built environments. While the socio-cultural influence of a bazaar determines the development of human relationships around it, its environmental components are also effective in responding to 'physical needs' of a populace, that is, the provision of necessities such as food and clothing as well as repair services. The relationship between environmental, social and cultural elements is found to be the most influential factor in increasing the sociality of the public space. In order to analyze bazaar socialization, the research methodology employed in this article comprises a descriptive survey that uses Delphi and Q methodology. According to the results, six key factors were identified: activity-behavioural-movement (ABM) components, physical-functional qualities, enviornmental impacts, physical components (PCs), cultural values (CVs), social cohesion and integration, diversity and spatial attraction. Crucially, the study also finds that the socialization of space is formed through the interaction between human experiences in place and the prevailing cultural forms within it, that is, the regional customs, traditions and overall 'way of life' of the native populace. Therefore, the cultural features of urban spaces are another important factor in their development. Studying these factors opens the possibility for facilitating greater levels of interaction and participation in public spaces in a manner that also accommodates different groups of people and their varying subcultures.